2020
DOI: 10.3390/ijms21186835
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins as Regulators of Migration, Invasion and Metastasis in Oral Squamous Cell Carcinoma

Abstract: Nearly 7.5% of all human protein-coding genes have been assigned to the class of RNA-binding proteins (RBPs), and over the past decade, RBPs have been increasingly recognized as important regulators of molecular and cellular homeostasis. RBPs regulate the post-transcriptional processing of their target RNAs, i.e., alternative splicing, polyadenylation, stability and turnover, localization, or translation as well as editing and chemical modification, thereby tuning gene expression programs of diverse cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 236 publications
(261 reference statements)
2
29
0
Order By: Relevance
“…Another identified target within this study was ESRP1. ESRP1 and ESRP2 play an important role in alternative splicing, and their expression is reduced during the EMT process [ 89 ]. It has been indicated that both were upregulated in dysplastic samples of OSCC, but their reduction was probably restricted in the cells that had a motile phenotype acquired during cancer invasion [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another identified target within this study was ESRP1. ESRP1 and ESRP2 play an important role in alternative splicing, and their expression is reduced during the EMT process [ 89 ]. It has been indicated that both were upregulated in dysplastic samples of OSCC, but their reduction was probably restricted in the cells that had a motile phenotype acquired during cancer invasion [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA–binding proteins (RBPs) control all aspects of post–transcriptional gene expression, including RNA splicing and editing, transport and localization, mRNA turnover and translation as well as miRNA biogenesis [ 1 , 2 ]. Therefore, they play essential roles during development, but also serve essential roles in tumor biology by modulating essentially all hallmarks of cancer [ 2 , 3 ]. De–regulation of RBPs is associated with a variety of human malignancies, including solid cancers, and targeting their expression or functions provides alternative strategies for cancer therapy [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…RBPs have been recognized as key regulators of transcription and post-transcriptional processing ( Janakiraman et al, 2018 ; Xu et al, 2019 ). A large body of work has shown that many RBPs have impacts on tumorigenesis and cancer cell survival ( Gao et al, 2020 ; Schultz et al, 2020 ; Weiße et al, 2020 ). Recent research into ncRNAs has revealed the existence of complex RBP-ncRNA interactions ( Jonas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%